A study of risk management in construction procurement project - Rozma Muhamad, Ridzwan (2014)
Construction is well known as a high-risk project as it involves in lot of uncertainty at which it must be carefully managed. In risk management it is contractor’s job to take the risk or to avoid the risk in their construction project. Some of them also may take some action in order to reduce the risk in their construction project. In construction project we always heard about the project is over schedule, project over budget, low quality of project, problems with the tender, problem with the client, problem with the sub-contractor and etc. Hence, this research is to study the possible risk in construction project, to determine the level of awareness of the procurement risk among contractor in construction project and lastly to identify the tools and technique used in managing risk of construction procurement process. This method of research is both qualitative and quantitative based. A questionnaire survey and interview was conducted to collect data from contractor Grade 1. Questionnaire surveys were distributed to 118 respondents from construction firms in Pasir Puteh area and three Grade 1 contractors was interviewed. The data collected is calculated using the percentage analysis. The result shown that financial, management, time and technical are the risk that involved in construction and the level of awareness of risk among the contractors are high. The contractors also have their own tools and technique in managing risk in construction procurement. In conclusion, the risk in construction is not a small issues in construction and the contractor must take quick action in managing the risk in construction